2018
DOI: 10.1007/978-1-4939-8760-3_17
|View full text |Cite
|
Sign up to set email alerts
|

A Nanodisc-Cell Fusion Assay with Single-Pore Sensitivity and Sub-millisecond Time Resolution

Abstract: During exocytosis, vesicles fuse with the plasma membrane and release their contents. The fusion pore is the initial, nanometer-sized connection between the plasma membrane and the cargo-laden vesicle. A growing body of evidence points towards the fusion pore being a regulator of exocytosis, but the shortcomings of current experimental techniques to investigate single fusion pores make it difficult to study factors governing pore behavior. Here we describe an assay that fuses v-SNARE-reconstituted nanodiscs wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…3A). To prevent exclusion of low conductance signals from analysis, we set a threshold close to the baseline and a minimum threshold-crossing duration to detect open subperiods in a burst [38,62]. Pore properties exhibit broad distributions ( Fig.…”
Section: Nanodisc-cell Fusionmentioning
confidence: 99%
See 2 more Smart Citations
“…3A). To prevent exclusion of low conductance signals from analysis, we set a threshold close to the baseline and a minimum threshold-crossing duration to detect open subperiods in a burst [38,62]. Pore properties exhibit broad distributions ( Fig.…”
Section: Nanodisc-cell Fusionmentioning
confidence: 99%
“…As for the ND-cell experiments, the composition of the outer plasma membrane is very different than that of the inner leaflet which a vesicle normally encounters during exocytosis. During ND-cell fusion, we actually do find some pores that have relatively stable conductances, but many of these are excluded from analysis because their amplitude/duration is lower than the set threshold [38,62]. Channellike pores that conform to the cut-off to be included in analysis are rare and the conductances are not uniform for a given condition (Fig.…”
Section: Nanodisc-black Lipid Membrane (Blm) Fusionmentioning
confidence: 99%
See 1 more Smart Citation
“…The zippering of the cognate vSNARE and tSNARE into SNAREpins brings the two membranes in close apposition and eventually opens up a fusion pore between the vesicle and the target compartment. The expansion of the fusion pore beyond 2 nm in diameter has been largely studied, both in vivo and in vitro ( 5 12 ). However, the efficiency of cargo release is likely to depend on the initial phase of the expansion process, that is, when the pore is below 2 nm.…”
mentioning
confidence: 99%
“…This scenario is only scarcely described in the literature because of technical difficulties required to accurately characterize such small pores. Recent studies based on in vitro electrophysiology approaches have shown the possibility to overcome these limitation1 using nanodisc-based fusion processes ( 7 11 ).…”
mentioning
confidence: 99%